2021
DOI: 10.1093/biolinnean/blab016
|View full text |Cite
|
Sign up to set email alerts
|

Social organization of otters in relation to their ecology

Abstract: Otter species are known to fluctuate intraspecifically from a solitary lifestyle to group-living arrangements. By examining what is known about habitat use and foraging style in otters of 13 different species, based on 93 studied sites, we assessed (1) the relationship between social habits and preferred habitats, (2) the relationship between species and prey preferences, and (3) the effect of predator avoidance on their social organization in order to assess the socio-ecological factors influencing otters. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 181 publications
0
4
0
Order By: Relevance
“…As far as we are aware there have been no reports of direct interspecific competition between any otter species. Indeed, sympatry facilitated by habitat, trophic and temporal separation has been widely documented between otter species across the globe, with sympatry in up to three otter species found in Thailand ( Ebensperger & Botto-Mahan, 1997 ; Krupa, Borker & Gopal, 2017 ; Kruuk et al, 1994 ; Lélias, Lemasson & Lodé, 2021 ; Somers & Purves, 1996 ). We found giant and neotropical otters were on average approximately 12 km and 3 h apart when detected on the same day, which indicates that competition is avoided both temporally and spatially.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we are aware there have been no reports of direct interspecific competition between any otter species. Indeed, sympatry facilitated by habitat, trophic and temporal separation has been widely documented between otter species across the globe, with sympatry in up to three otter species found in Thailand ( Ebensperger & Botto-Mahan, 1997 ; Krupa, Borker & Gopal, 2017 ; Kruuk et al, 1994 ; Lélias, Lemasson & Lodé, 2021 ; Somers & Purves, 1996 ). We found giant and neotropical otters were on average approximately 12 km and 3 h apart when detected on the same day, which indicates that competition is avoided both temporally and spatially.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these studies agreed on the relatively low density of Eurasian otter populations compared to those reported for terrestrial mesocarnivores 21 , 22 but this is also dependent on habitat specialization. Although the otter is generally considered to be a solitary territorial species 11 , 23 , a recent meta-analysis 24 showed that in certain situations of high vegetation cover and prey availability, otter populations can exhibit other social patterns, including flexible territoriality and matrilineal groups. Quaglietta et al 25 found such patterns in southern Portugal, with some plasticity in social behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Of 13 extant species of otters ( Lutrinae ), several are social (Lodé et al, 2021), and at least three are cooperative breeders: giant ( Pteronura brasiliensis ), small-clawed ( Aonyx cinereus ), and smooth-coated ( Lutrogale perspicillata ) otters (Bungum et al, 2021; Lélias et al, 2021). Smooth-coated otters typically live in family groups (“romps”) that consist of a breeding pair and their offspring of different ages (Bungum et al, 2021).…”
Section: Introductionmentioning
confidence: 99%